2007
DOI: 10.1215/15228517-2007-009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the amplicon on chromosomal segment 4q12 in glioblastoma multiforme

Abstract: A subset of glioblastomas (GBMs) carry gene amplifications on chromosomal segment 4q12. To characterize this amplicon in detail, we analyzed a set of 100 samples consisting of 65 GBMs, 10 WHO grade III astrocytomas, 12 oligodendrogliomas, and 13 glioma cell cultures. We applied multiplex ligation-dependent probe amplification to determine the gene dosage of PDGFRA, KIT, and KDR and the flanking genes USP46, RASL11B, LNX1, CHIC2, SEC3L1, and IGFBP7. The amplicon was highly variable in size and copy number and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 16 publications
6
47
0
Order By: Relevance
“…It has been suggested that the MDM4 gene is the main amplification target in this amplicon (Riemenschneider et al, 2003) although it is not always coamplified in gliomas with hCNA of 1q32 [this study and see, e.g., (Rickman et al, 2001)]. Because single amplicons may contain several causal genes (Holtkamp et al, 2007) and the observation that MDM4 is not always coamplified, the 1q32 amplicon may contain additional oncogenes.…”
Section: Integrated Genomic Profiling Identifies Rbbp5 As a Candidatementioning
confidence: 73%
“…It has been suggested that the MDM4 gene is the main amplification target in this amplicon (Riemenschneider et al, 2003) although it is not always coamplified in gliomas with hCNA of 1q32 [this study and see, e.g., (Rickman et al, 2001)]. Because single amplicons may contain several causal genes (Holtkamp et al, 2007) and the observation that MDM4 is not always coamplified, the 1q32 amplicon may contain additional oncogenes.…”
Section: Integrated Genomic Profiling Identifies Rbbp5 As a Candidatementioning
confidence: 73%
“…48 Collectively, the GBMX tumor panel provides a valuable resource with which to dissect the biology of the amplicons described herein, as it is becoming clearer that multiple genes encoded within amplicons play important roles in driving tumor biology. 49,50 This in turn may lead to the development of novel therapeutic agents and strategies for disease treatment.…”
Section: The Mrc Expression Signature In Gbmx Tumorsmentioning
confidence: 99%
“…It was also reported that KIT and PDGFRA could be altered in ALM by gene amplification mechanisms of their 4p12 locus [18][19][20]. Besides these two oncogenes, this locus also harbors another important oncogene, KDR, also known as VEGFR2 (vascular endothelial growth factor receptor-2 gene) [21,22]. Importantly, many of the mutated molecules in ALM have emerged for therapeutic targets, such as BRAF, KIT/ PDGFR, and VEGFR2 [23][24][25].…”
Section: Introductionmentioning
confidence: 99%